Strategi Guru dalam Mengelola Emosi Peserta Didik di SD Inpres Bumi Bahari Kota Palu - Nur Nadia Tenong; Aniati Aniati; Mirnawati Mirnawati; A. Ardiansyah (Institut Nalanda, 2026)
This study aims to describe the teacher’s strategies in managing students’ emotions and the impact of these strategies at SD Inpres Bumi Bahari, Palu City. Emotional management in elementary education is an essential aspect in creating a conducive and effective learning environment. This research uses a qualitative approach with a descriptive method. Data were collected through interviews with the principal, classroom teacher, students, and parents. The results show that teachers apply several dominant strategies in managing students’ emotions, including calm and empathetic communication, continuous guidance and advice, conflict mediation between students, and exemplary behavior in emotional control. These strategies are implemented consistently in daily classroom activities. The findings indicate that the implementation of these strategies has a positive impact on students’ emotional development. Students become more emotionally stable, classroom conflicts decrease, and the learning environment becomes more conducive and comfortable. In addition, students demonstrate improved social attitudes such as willingness to apologize, respect for others, and better emotional control. These results imply that teacher involvement plays a crucial role in shaping students’ emotional regulation and social behavior in elementary school settings. Therefore, strengthening teacher competencies in emotional management is highly recommended to support holistic student development.